Pro-angiogenic Role of Insulin: From Physiology to Pathology - Escudero, Carlos A.; Herlitz, Kurt; Troncoso, Felipe; Guevara, Katherine; Acurio, Jesenia; Aguayo, Claudio; Godoy, Alejandro S.; González, Marcelo (Frontiers in Physiology, 2017)
The underlying molecular mechanisms involve in the regulation of the angiogenic process by insulin are not well understood. In this review article, we aim to describe the role of insulin and insulin receptor activation on the control of angiogenesis and how these mechanisms can be deregulated in human diseases. Functional expression of insulin receptors and their signaling pathways has been described on endothelial cells and pericytes, both of the main cells involved in vessel formation and maturation. Consequently, insulin has been shown to regulate endothelial cell migration, proliferation, and in vitro tubular structure formation through binding to its receptors and activation of intracellular phosphorylation cascades. Furthermore, insulin-mediated pro-angiogenic state is potentiated by generation of vascular growth factors, such as the vascular endothelial growth factor, produced by endothelial cells. Additionally, diseases such as insulin resistance, obesity, diabetes, and cancer may be associated with the deregulation of insulin-mediated angiogenesis. Despite this knowledge, the underlying molecular mechanisms need to be elucidated in order to provide new insights into the role of insulin on angiogenesis.